Toward Collective Self-Awareness and Self-Expression in Distributed Systems. - Amoretti, Michele; Cagnoni, Stefano (Computer (00189162), 2015)
Simultaneously applying hierarchy and recursion enables self-awareness and self-expression in distributed systems, which can provide greater efficiency and scalability in tasks such as network exploration and message routing.